Proper disposition and denial of marriage: Canon 843 - Espelage, Arthur J. (CLSA advisory opinions, 2001-2005, 2001)
The pastor of a parish, citing his responsibility for the care of souls and the proper administration of the sacraments, requires that each couple requesting the sacrament of marriage in his church sign an oath, then inserted into the pre-nuptial file, that the couple, once married, will never employ artificial contraception as birth control in their married life. Those who refuse to take the oath and to sign the document are refused the celebration of marriage in that particular parish, based on the pastor's judgment that they lack proper disposition to celebrate marriage. The policy is commonly known by parishioners in this particular parish. One young engaged couple consider themselves good Catholics, but wish to know if the pastor can make such a demand in his parish.